Characteristics of individuals with high and low driving anger - Filetti, Linda Baker, author; Deffenbacher, Jerry L., advisor; Rickard, Kathryn M., committee member; Viney, Wayne, committee member; Anderson, Jennifer, committee member (Colorado State University. Libraries, 2000)
The study examined the relationship of personality factors to aggressive and risky driving and tested predictions of state-trait anger theory applied to driving anger. It also assessed implications for interventions to reduce driving anger by comparing two groups of introductory psychology students who were high in trait driving anger, one perceiving themselves as having a problem with driving anger and seeking counseling for those problems (high anger-problem or HAP) and another not perceiving themselves as having a problem with driving anger (high anger-no problem or HANP), to a low anger group who did not perceive themselves as having a problem with driving anger (low anger-no problem or LANP). Predictions of state-trait anger theory were generally confirmed. Compared to low anger drivers, high anger drivers: (a) reported anger in response to a greater number of driving situations; (b) were more frequently and (c) intensely angered when driving; (d) expressed their driving anger in more hostile/aggressive and (e) less adaptive/constructive ways; (f) engaged in more aggressive and (g) risky behavior while driving, and (h) experienced more accident-related consequences. Findings were confirmed by surveys, logs of emotion and behavior while driving, and simulations involving visualization of provoking events. High anger participants also reported more general anger and impulsiveness and more negative, less constructive ways of expressing general anger. Generally, HAP and HANP drivers were similar, but a few differences suggested that HAP drivers were somewhat more angry, aggressive drivers. Thus, both high anger groups were at elevated risk for angry, aggressive and risky driving, but implications for intervention are different. Because HAP participants saw themselves as having a problem and wanted counseling, they can be addressed with psychotherapeutic interventions (e.g., Deffenbacher, Huff, Lynch, Oetting, & Salvatore, in press). Given their elevations on general anger and impulsiveness, counseling should address these characteristics as well However, since the HANP group did not perceive themselves as having a personal problem with driving anger, psychotherapeutic interventions are not appropriate. Interventions for this group should focus first on these self-perceptions and increase awareness of risk status and readiness for change.
Keywords: personality; psychotherapy; behavioral sciences; personality psychology; behavioral psychology; clinical psychology